Crianza de animales domésticos como factor de riesgo de fascioliasis humana - Valderrama P., Aldo (2019)
The aim of this study was to determine the association of fascioliasis with the breeding of animals, housing characteristics and food consumption of children in the district of Santa María de Chicmo, Apurimac, Peru. Serological samples were taken from 493 children aged 6 to 16 years, males and females, with the informed consent of their parents. The prevalence, determined by the immunoblot technique was 5.3% (95% CI = 3.2% -7.4%, 26/493). The univariate analysis showed that the breeding of cattle and cats, and raising three or more pigs were factors associated with fascioliasis. The breeding of more than five sheep resulted as a protection factor. Fascioliasis in children was not associated with the characteristics of the dwellings or the consumption of food. It is concluded that the district of Santa María de Chicmo is mesoendemic for fascioliasis in children, and that the rearing of some species of domestic animals involves risk of human fascioliasis.